2018
DOI: 10.1007/s00132-018-3573-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of arthroscopic management of popliteal cysts with or without additional posterior open cystectomy

Abstract: In comparison to arthroscopic decompression of cysts and management of intra-articular pathologies alone, the additional posterior open cystectomy reduced the recurrence of popliteal cysts, although it took longer to perform and brought more perioperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…With the improvement of the mean Lysholm score from 54 to 86 at a mean follow-up of 39 months reported in this study, the results are comparable with the abovementioned literature, with longer follow-up. On contrary, in the study of Xinxian et al, the authors reported improvement of the Lysholm score in arthroscopically treated group from the preoperative mean of 76.6 to 86.3 at the mean of 33.3 months follow-up [ 20 ]. While authors stated that all patients “complained of symptomatic knee joint pain and/or joint limitation,” a lot higher preoperative Lysholm score than in the rest of the literature can be seen, making direct comparison of outcomes difficult [ 7 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the improvement of the mean Lysholm score from 54 to 86 at a mean follow-up of 39 months reported in this study, the results are comparable with the abovementioned literature, with longer follow-up. On contrary, in the study of Xinxian et al, the authors reported improvement of the Lysholm score in arthroscopically treated group from the preoperative mean of 76.6 to 86.3 at the mean of 33.3 months follow-up [ 20 ]. While authors stated that all patients “complained of symptomatic knee joint pain and/or joint limitation,” a lot higher preoperative Lysholm score than in the rest of the literature can be seen, making direct comparison of outcomes difficult [ 7 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a retrospective study by Xinxian et al including 65 patients with symptomatic popliteal cysts over eight years compared the arthroscopic management of intra-articular pathologies and decompression of the cyst with and without open cyst wall resection, revealing better clinical outcomes and lower recurrence rates when the latter is included, but with a longer surgical time and postoperative complications at a mean 33.3 months follow-up [15]. Although there was no recurrence during the one-year follow-up of the present case report, it represents the most common complication reported as high as in 63% of the cases [9,16].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Zhou et al pooled data from 11 studies, comparing different surgical methods in therapy of popliteal cyst, showing that following these principles yielded satisfactory outcomes in more than 95% of the patients, but data was insufficient to support arthroscopic over open approach [ 5 ]. Likewise, a retrospective study by Xinxian et al including 65 patients with symptomatic popliteal cysts over eight years compared the arthroscopic management of intra-articular pathologies and decompression of the cyst with and without open cyst wall resection, revealing better clinical outcomes and lower recurrence rates when the latter is included, but with a longer surgical time and postoperative complications at a mean 33.3 months follow-up [ 15 ]. Although there was no recurrence during the one-year follow-up of the present case report, it represents the most common complication reported as high as in 63% of the cases [ 9 , 16 ].…”
Section: Discussionunclassified
“…Posterior open surgery has traditionally been used for symptomatic popliteal cysts with ineffective conservation 6,9 . This type of operation not only carries risk of nerve damage, but also requires longer operation times and is more prone to perioperative complications [16][17][18] . In addition, this method only focuses on the cyst itself, and does not consider the intra-articular pathology and unidirectional valve mechanism, so the cyst may easily recur.…”
Section: Introductionmentioning
confidence: 99%